Sea Transport Demand in the Mainer Spanish Ports - Maria del Mar Cerban; Maria del Pilar Lopez-Ortega; Mercedes Villanueva; Javier Rojas Andrades (European Regional Science Association (ERSA), 2004)
The objective of the present paper is to analyse the progress of data in shipping demand between 1993 and 2002 in the most important spanish ports, in the others words, those ports that are under State Ports protection, and their relation with Gross Domestic Product (GDP) as well as Freight Index. The methodology that has been used to draw the shipping demand function up is the traditional one, due to we use added variables , i.e. they mean the global behaviour of a certain group of individuals. To prepare this paper, the demand account of sea transport services has been divided in three groups, in function of cargo types: General Merchandise, Solid Bulks and Liquid Bulks. The reason why we use this kind of division is that Principals Institutions in Sea Transport bring their statistics down in this way. Similarly, we pretend to analyse the evolution in the share of different cargos in the whole shipping demand in the period mentioned before (1993/2002). The particular demand function for each cargo type in a certain year is going to be in function of the GDP and the freight rate in that year. The Freight Index used depends on the cargo analysed. So, in case of general merchandise it has been used the liner freight index, since this cargo type use to be transported in liner terms. Usually, Freight Conferences fix prices in this navigation. In case of Solid and Liquid Bulks, we have chosen dry cargo and tanker cargo freight index respectively. The standard procedure to transport these kind of bulks is by "tramp" navigation. In "tramp" navigation, prices use to be fixed by time freight, when ships services are contracted for a limited period of time, or travel freight, when ship services are contracted for a particular trip.
Keywords: 330